A Study of Senior High Schools in Palembang: Students’ Errors in Writing - izza choirun nisa (Universitas Galuh, 2023)
This research was intended to find out an error analysis of students' writing of eleventh grade of students of three senior high schools in Palembang. Quantitative content analysis research is conducted in this research as the methodology research. This research was conducted in three senior high schools in Palembang, namely, (1)SMA Muhammadiyah 6 Palembang which is accredited A, (2) SMA Nurul Amal Palembang which is accredited B, (3), SMA Muhammadiyah 8 Palembang which is accredited C. The total of participant of this research is 30 students. In collecting data, the researcher used writing sheet test and error checklist as the instrument of this research. The data was analyzed by using method of analyzing error by Ellis. The results of this research showed the errors of writing aspects on students writings of eleventh grade students of three high senior high schools in Palembang, namely, first is content errors, second is paragraph organizations errors, third is vocabulary error, forth is mechanic error, and fifth is grammar error. From the findings of this research could be conclude that some of eleventh-grade students in senior high schools in Palembang have less knowledge or lack information about five writing aspects as the essential knowledge to write text.